2020
DOI: 10.3390/app10144948
|View full text |Cite
|
Sign up to set email alerts
|

Using Synthetic Data to Improve and Evaluate the Tracking Performance of Construction Workers on Site

Abstract: Vision-based tracking systems enable the optimization of the productivity and safety management on construction sites by monitoring the workers’ movements. However, training and evaluation of such a system requires a vast amount of data. Sufficient datasets rarely exist for this purpose. We investigate the use of synthetic data to overcome this issue. Using 3D computer graphics software, we model virtual construction site scenarios. These are rendered for the use as a synthetic dataset which augments a self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…10. This problem may be solved by adding virtual cameras and sensors to the 3D model to simulate Lidar scanning through point cloud simulation software (Blender et al) [29], and setting the location of the virtual cameras and scanning parameters to maximize the restoration of the real scanning scene.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…10. This problem may be solved by adding virtual cameras and sensors to the 3D model to simulate Lidar scanning through point cloud simulation software (Blender et al) [29], and setting the location of the virtual cameras and scanning parameters to maximize the restoration of the real scanning scene.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…This cluster encompasses the studies that use existing deep-learning models, such as YOLO, CNN, R-CNN, CNN+LSTM, and Faster R-CNN, for the recognition of diverse construction site activities (Luo et al 2018, detection of unsafe worker behaviour on the construction site (Ding et al 2018), detection of workers wearing PPE (e.g., safety helmet, safety waist) (Fang et al 2018b, Mneymneh et al 2019, Neuhausen et al 2020, and performance evaluation of construction workers on site. Each of these deep-learning models has been shown to achieve high accuracy and speed.…”
Section: Construction Site Activity and Worker Monitoring Using Deep ...mentioning
confidence: 99%
“…Generated synthetic images are proven to be effective in improving DNN training. Since labels are extracted automatically in this approach, data generation is a seamless effort (Neuhausen et al, 2020); thus, an unlimited number of synthetic data is accessible as seen in the SYNTHIA dataset (Ros et al, 2016).…”
Section: Synthetic Datamentioning
confidence: 99%
“…Following the same approach, Mahmood et al (Mahmood et al, 2022) developed a synthetic dataset for training DNN models that estimated the 3D pose of an excavator. In a very recent study by Neuhausen et al (Neuhausen et al, 2020), synthetically generated images are leveraged to train DNNs with a focus on human worker detection and tracking model. A comparative study of the developed model on both synthetic and real-world data identified the synthetic images as a viable solution for vision-based DNN training.…”
Section: Synthetic Datamentioning
confidence: 99%